Report on the Regional WCRP/SPARC Workshop with focus on the Southern Hemisphere and South America - Vera, Carolina Susana (2013)
From 26-27 November 2012 the Workshop on Southern Hemisphere and South American Climate was held in Buenos Aires, Argentina, back-to-back with the SPARC SSG Meeting, hosted by the “Centro de Investigaciones del Mar y la Atmósfera” (CIMA). [...]